3-D rolling processing analysis by Fast Multipole Boundary Element Method. (September 2016) - Yu, Chunxiao; Liu, Deyi; Zheng, Yongjiang; Shen, Guangxian
Abstract: This paper presents the numerical analysis of 3-D rolling processing by a kind of Fast Multipole Boundary Element Method (FM-BEM). The FM-BEM combines the Fast Multipole Method (FMM) and Boundary Element Method (BEM), for which the fundamental formulations and numerical implementations are obtained. Then a node-to-surface frictional contact model is provided and contact constraints are linearized. For the solution system, an improved Generalized Minimal Residual Algorithm (GMRES) is employed as a fast solver. Combined with high performance computing, a cold rolling process of 2030 four-high mill with a width-to-thickness ratio of 1850 is successfully simulated, and comprehensive new rolling information is obtained. Numerical results show that the presented FM-BEM requires less artificial assumptions, and it has higher precision and efficiency as compared to the traditional BEM, Finite Element Method (FEM) and Finite Difference Method (FDM). It is a breakthrough progress in the simulation of rolling engineering, which is of great significance.